Hubungan Pemberian ASI terhadap Status Gizi Bayi Usia 4-6 Bulan di UPT Kesmas Sukawati I - I Gusti Ayu Avinya Chintya Devi; Ni Kadek Elmy Saniathi; Ni Putu Diah Witari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between Breastfeeding and the Nutritional Status of Babies Aged 4-6 Months at UPT Public Health Sukawati I] Nutritional problems in Indonesia are a double burden, both due to deficiency and excess nutrition. Lack of nutrition at an early age can lead to impaired child development. Efforts have been made to overcome nutritional problems, one of which is through exclusive breastfeeding. Data in Gianyar Regency shows that the scope of exclusive breastfeeding has increased but is not accompanied by a significant decrease in cases of malnutrition and malnutrition. This study aims to find out the correlation of breastfeeding on the nutritional status of infants aged 4-6 months at UPT Kesmas Sukawati I. This research is an analytic observational study applying a cross sectional research design carried out in January-June 2021, with a sample of 68 infants. The sample was selected using the consecutive sampling method, which is a sample selection according to inclusion and exclusion requirements. The research data was then analyzed with univariate and bivariate analysis. The bivariate test used was the chi-square test and fisher's exact test aimed at finding the correlation of two categorical-scale variables. p <0.05 indicates a significant correlation between the two variables. The results showed that there was a significant correlation between breastfeeding and poor nutritional status (p=0.000) and good-over-nutrition status (p=0.043), there was no significant correlation between breastfeeding and less-than-good nutritional status (p= 0.137). In conclusion, there is a significant correlation between breastfeeding for undernourished, well-nourished and good-nourished and over-nourished infants aged 4-6 months.